Effectiveness of online grammar checker to improve secondary students' English narrative essay writing - Jayavalan, Kalpana; Mohamed Razali, Abu Bakar (Malaysia Association of Research and Education for Educators, 2018)
The purpose of this study is to investigate whether a grammar checker application, i.e., Grammarly, has positive effects in the narrative writing of the secondary school students. In the Malaysian context of English language learning, the major difficulty that the students encounter would be writing and it has always been the reason why students cannot excel in the examination (Chuo, 2004). Thus, this study explores the effectiveness of Grammarly, a grammar checker computer application, in aiding secondary students’ narrative writing. The research is guided by the theories and principles of Vygotsky’s (1978) Zone of Proximal Development (ZPD) and Knowles’ (1984) Self-Directed Learning approach. This study employs a quantitative research methodology, which is quasi experimental approach with non-equivalent control group design. Participants in this study were 60 form four students from two different classes in a public primary school in a state in western part of Peninsular Malaysia. They were divided equally into an experimental, and a control group and the students came from the same age group and English language, particularly English writing proficiency. The data was gathered for research through pre-and post-tests which were then analysed using paired sample T-Test. Continuous quantitative type of observation data (i.e., scores from writing exercises) was also obtained from their engagement with series of treatment using the Grammarly grammar checker application. The findings revealed that the grammar checker aids the narrative writing among the students in the experimental group, especially in sentence construction. The results of this study revealed that at P= .000 alpha level the grammar checker does aid in the writing of narrative essay among the Form 4 students, particularly on their use of correct grammar functions (namely subject-verb agreement, sentence structure, spelling, and punctuation). The researchers call for more future research on the grammar checker as it holds opportunities for the students to progress in their narrative writing. Using grammar checkers might be a great shift from a traditional learning approach to a more independent self-directed learning approach among students.